2016
DOI: 10.1159/000447885
|View full text |Cite
|
Sign up to set email alerts
|

SGK1, the New Player in the Game of Resistance: Chemo-Radio Molecular Target and Strategy for Inhibition

Abstract: The serum- and glucocorticoid-regulated kinase (SGK) family consists of three members, SGK1, SGK2 and SGK3, all displaying serine/threonine kinase activity and sharing structural and functional similarities with the AKT family of kinases. SGK1 was originally described as a key enzyme in the hormonal regulation of several ion channels and pumps. Over time, growing and impressive evidence has been accumulated, linking SGK1 to the cell survival, de-differentiation, cell cycle control, regulation of caspases, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 88 publications
(133 reference statements)
2
64
0
Order By: Relevance
“…Moreover, we found that suppression of miR-124 strikingly reversed XIST knockdownmediated repression on DOX resistance in DOX-resistant CRC cells. SGK1, belonging to the AGC family of serine/threonine protein kinases, has been suggested to be overexpressed and associated with cell proliferation, apoptosis, invasiveness, motility, epithelial to mesenchymal transition, adhesiveness and chemoresistance in a variety of epithelial tumors [20,36]. Amato et al firstly revealed the association of SGK1 and doxorubicin-induced apoptosis in kidney cancer cells [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we found that suppression of miR-124 strikingly reversed XIST knockdownmediated repression on DOX resistance in DOX-resistant CRC cells. SGK1, belonging to the AGC family of serine/threonine protein kinases, has been suggested to be overexpressed and associated with cell proliferation, apoptosis, invasiveness, motility, epithelial to mesenchymal transition, adhesiveness and chemoresistance in a variety of epithelial tumors [20,36]. Amato et al firstly revealed the association of SGK1 and doxorubicin-induced apoptosis in kidney cancer cells [37].…”
Section: Discussionmentioning
confidence: 99%
“…5A, binding sites of miR-124 were identified in the 3'UTR of SGK1 mRNA. SGK1 has been reported to participate in cell survival, de-differentiation, cell cycle control, apoptosis, as well as chemo-and radio-resistance in various malignancies [20]. Moreover, a recent document points out that SGK1 is essential and rate limiting in the control of precursor miRNA nuclear export Cellular Physiology and Biochemistry Cellular Physiology and Biochemistry [21].…”
Section: Xist Positively Regulated Sgk1 Expression By Interacting Witmentioning
confidence: 99%
“…Indeed, this assumption was postulated previously in various tumor cell models by analyzing the correlation of EMT with actin signaling and migration [13, 19-27]. Moreover, previous studies showed that the Serum glucocorticoid kinase 1 (Sgk1) plays a key role in EMT in colon carcinoma [28]. Furthermore, Sgk1 regulates epi-genomic re-alignment and drug-resistance through the control of GTP-proteins RANBP1 and RAN [29].…”
Section: Discussionmentioning
confidence: 86%
“…Both SGK1 and TNFAIP8 reportedly participate in apoptosis evasion, cell survival, chemo resistance and tumor progression (Fig. 5E) (3033) (34). Western blotting analysis validated select ENZ- and OLA-upregulated pro-apoptotic genes and ENZ-downregulated and OLA-upregulated SGK1 and TNFAIP8 (Fig.…”
Section: Resultsmentioning
confidence: 99%